3T MRI characteristics of the palatine tonsil in brachycephalic dogs. (8th November 2021) - Köhler, Claudia; Fromme, Vivian; Kohl, Stefan; Winter, Karsten; Weidauer, Jenny; Kiefer, Ingmar
Abstract: Background: Investigation of the MRI characteristics of the palatine tonsil in brachycephalic dogs in 3T high‐field system. Methods: Eighty‐five brachycephalic dogs and 37 normocephalic dogs were divided into five groups: group 1 French bulldogs (FBs) with neurological clinical signs ( n = 37), group 2 FBs with brachycephalic obstructive airway syndrome (BOAS) ( n = 22), group 3 pugs with neurological clinical signs ( n = 17), group 4 pugs with BOAS ( n = 9) and group 5 normocephalic dogs ( n = 37). Cross‐sectional area and volume measurements were performed, and tonsillar margination and contour, shape, signal intensity and homogeneity/heterogeneity of the palatine tonsils were evaluated and compared. Results: Cross‐sectional area and volume measurements of the tonsils showed no significant differences between brachycephalic and normocephalic dogs with the exception of the dogs of group 2 (FB BOAS), which showed relatively high volume and large cross‐sectional area in comparison to other groups. In 87% of the brachycephalic animals, the tonsils were well defined. A smooth contour was detectable in 91.8% and a rounded shape in 94.7% of brachycephalic dogs. Signal intensity was assessed as hyperintense in relation to the musculature and iso‐ to hyperintense to the soft palate. Heterogeneous appearance was described in 86.9% of the brachycephalic animals. Conclusions: The MRI characteristics of the tonsils of brachycephalic dogs do not differ considerably from those of normocephalic dogs. In FBs with distinct clinical signs of obstructive airway syndrome, increase in cross‐sectional area and volume of the tonsils was detected.